2012
DOI: 10.1074/jbc.m112.386912
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Suppression of Endoplasmic Reticulum Stress Promotes an Antiatherogenic Monocyte/Macrophage Phenotype in Type 2 Diabetic Patients

Abstract: Background:Interactions between environmental conditions and monocyte phenotype are critical for the development of vascular complications in diabetes. Results: Modulation of ER stress by vitamin D controls monocyte/macrophage phenotype and vascular adhesion. Conclusion: Vitamin D is a natural ER stress reliever that promotes an anti-inflammatory monocyte/macrophage phenotype. Significance: Vitamin D is a potential therapy to reduce vascular complications in diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 60 publications
2
106
0
3
Order By: Relevance
“…This resulted from downregulation of JNK activity, improved insulin signaling, reduced oxidized LDL-derived cholesterol uptake, as well as suppression of macrophage endoplasmic reticulum (ER) stress and promotion of an antiatherogenic monocyte/macrophage phenotype (51,59). More recently, Szeto et al (66) showed that VDR deficiency (i.e., VDR Ϫ/Ϫ genetic background) accelerated the atherosclerotic process in the low-density lipoprotein receptor-deficient (LDLR Ϫ/Ϫ ) mouse.…”
Section: Expression Of Vdr and 1␣-hydroxylase Genes In Heartmentioning
confidence: 95%
“…This resulted from downregulation of JNK activity, improved insulin signaling, reduced oxidized LDL-derived cholesterol uptake, as well as suppression of macrophage endoplasmic reticulum (ER) stress and promotion of an antiatherogenic monocyte/macrophage phenotype (51,59). More recently, Szeto et al (66) showed that VDR deficiency (i.e., VDR Ϫ/Ϫ genetic background) accelerated the atherosclerotic process in the low-density lipoprotein receptor-deficient (LDLR Ϫ/Ϫ ) mouse.…”
Section: Expression Of Vdr and 1␣-hydroxylase Genes In Heartmentioning
confidence: 95%
“…90 Moreover, 1a,25(OH) 2 D 3 acting as a natural endoplasmic reticulum stress reliever was found to induce an M1 antiatherogenic macrophage/monocyte phenotype over M2 (with increased cholesterol uptake and deposition) and to decrease mRNA expression of the monocyte adhesion molecules PSGL-1, β(1)-integrin, and β(2)-integrin, resulting in an increase of monocyte adhesion to activated endothelium. 91 Moreover, 1a,25(OH) 2 D 3 dose-dependently inhibited the production of IL-6 and TNF-α by monocytes, an effect exerted at a posttranscriptional level, and possibly contributed to the aforementioned suppression of Th1 proatherogenic immune response. 92 In addition to their immunoregulatory effects, monocytes are implicated in the development of atherothrombotic lesions by regulating coagulant and anticoagulant factors.…”
Section: Effects Of Vitamin D On Immune Cellsmentioning
confidence: 99%
“…Stimulation of ER stress induces responses to improve protein folding, but persistent stress triggers further inflammation through NF-kB and c-Jun N-terminal kinase activation (JNK) activation, increasing foam cell formation and inducing plaque necrosis in advanced atherosclerotic lesions (Hotamisligil, 2006; Ozcan and Tabas, 2010). Vitamin D is a natural macrophage ER stress reliever (Riek et al, 2012). Vitamin D receptor (VDR) is present in almost all cells of the immune system, and vitamin D deficiency is widely prevalent and has emerged as a potential contributor to the pathophysiology of T2DM and CVD (Holick, 2007; Norman and Powell, 2014; Veldman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%